A comparative study of sclero-corneal and clear corneal tunnel incision in manual small-incision cataract surgery - Archana, S; Khurana, AK; Chawla, U (Nepalese Journal of Ophthalmology, 2011)
Background: Cataract surgery techniques have improved a lot over the years from couching to the latest micro-incision cataract surgery. Objectives: To compare the temporal sclero-corneal and clear corneal tunnel incisions in patients undergoing manual small-incision cataract surgery (SICS) with respect to the surgically-induced astigmatism. Materials and methods: The present study included 60 patients who underwent manual SICS with posterior chamber intraocular lens implantation. Group A comprised of 30 patients, selected randomly, who underwent sutureless manual SICS through 6 mm curvilinear clear corneal tunnel incision made temporally and Group B comprised of 30 patients, selected randomly, who underwent sutureless manual SICS through 6 mm straight sclero-corneal tunnel made temporally. The patients were assessed at 1 week, 2 weeks, 1 month and 2 months post-operatively and visual acuity and keratometry findings were recorded. The amount of surgically induced astigmatism was calculated using Holladay’s formula. Statistics: Numerical data were compared between the two groups using unpaired Student’s t-test. The p value of < 0.50 was considered significant. Results: The mean induced astigmatism in Group A was 2.69 ± 0.84 D at 1 week, 2.31 ± 0.77 D at 2 weeks; 2.03 ± 0.82 D at 4 weeks and 1.98 ± 0.54 D at 8 weeks post-operatively. In group B, it was 1.85 ± 0.62 D, 1.56 ± 0.54 D, 1.35 ± 0.49 D and 1.34 ±0.45 D at 1 week, 2 weeks, 4 weeks and 8 weeks postoperatively. Uncorrected visual acuity (UCVA) of 20/ 20 was seen in 20 % of patients in group A and in 40 % in group B at 8 weeks postoperatively. Conclusion: Surgically-induced astigmatism is significantly higher in clear corneal manual SICS than in sclero-corneal. Our study confirmed the safety and improvement in visual acuity after small-incision cataract surgery using sclero-corneal tunnel incision. Key words: astigmatism; sclero-corneal; clear corneal tunnel; extra-capsular cataract surgery; small incision cataract surgery DOI: 10.3126/nepjoph.v3i1.4273Nepal J Ophthalmol 2011;3(5):19-22